2019
DOI: 10.1002/ncp.10274
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition in Children With Chronic Disease

Abstract: Malnutrition occurs when nutrient intake does not meet the needs for normal body functions and as a consequence leads to alterations of growth and development in children. Chronic illness puts children at risk for developing malnutrition. Because of children's rapid periods of growth and development, early diagnosis, prevention, and management of malnutrition are paramount. The reasons for malnutrition in children with chronic disease are multifactorial and are related to the underlying disease and nonillness-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 125 publications
2
44
0
4
Order By: Relevance
“…Furthermore, children with congenital heart anomalies often struggle with vomiting and feeding tolerance and consequently develop an oral aversion. Some well-understood postoperative risk factors for malnutrition in children with CHD are frequent interruptions of feeding, vocal cord dysfunction, chylothorax, and those with single ventricle disease that is at risk for experiencing a protein-losing enteropathy [7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, children with congenital heart anomalies often struggle with vomiting and feeding tolerance and consequently develop an oral aversion. Some well-understood postoperative risk factors for malnutrition in children with CHD are frequent interruptions of feeding, vocal cord dysfunction, chylothorax, and those with single ventricle disease that is at risk for experiencing a protein-losing enteropathy [7].…”
Section: Introductionmentioning
confidence: 99%
“…The improvements in nutritional care, which have led to increased survival and well-being of many children with chronic disease, have been achieved by effective collaborations between scientists, clinicians, and industry [1]. However, in the critically important area of infant and young child nutrition in the general population, partnership working, especially between the WHO and the infant food industry, has a history of acrimony and division, and consequently infant feeding issues relating to policy and practice that were prominent 4 decades ago are still current today [2].…”
mentioning
confidence: 99%
“…Children with chronic disease are at risk of malnutrition due to increased caloric needs, malabsorption, altered nutrient utilization and limitations in nutrient provision. The degree to which pubertal development is affected in chronic illness depends on the type of disease and its severity 26 . Undernutrition is associated with a significant delay in attaining pubertal levels of IGF‐1, LH, FSH and sex steroid hormones, as well as with low leptin levels 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Undernutrition is associated with a significant delay in attaining pubertal levels of IGF‐1, LH, FSH and sex steroid hormones, as well as with low leptin levels 27 . In children affected by CF, risk factors for malnutrition are resting energy expenditure, chronic inflammation, malabsorption secondary to pancreatic insufficiency, fat‐soluble vitamin deficiencies, diabetes and decreased appetite 26 . It has been demonstrated that chronic inflammation in CF, despite good clinical status, is an important modulator of the IGF/IGFBP system, and it represents a possible mechanism for peripheral resistance to growth hormone (GH).…”
Section: Discussionmentioning
confidence: 99%